PENGEMBANGAN BAHAN AJAR BERBASIS ADVANCED ORGANIZER BERVISI SETS (SCIENCE, ENVIRONMENT, TECHNOLOGY, AND SOCIETY) PADA MATERI KOLOID - Arina Dwi Aprilia; Rilia Iriani; Siti Halimah Nurdiniah (QUANTUM: Jurnal Inovasi Pendidikan Sains, 2018)
Abstract. Quality of teaching materials is needed in learning. One of the teaching materials development techniques is development of teaching materials based on the learning model. Learning models that can be applied in teaching materials development are Advanced Organizer with SETS (Science, Environment, Technology, and Society) vision. The research development model used is 4D and implemented in SMA Negeri 1 Kuala Kapuas on colloid material. The sample in this research consisted of 12 students of XI IPA for small group test, 28 students of XI IPA 3 and 28 students of XI IPA 4 for limited field-testing. Data collection techniques use expert validation sheets, learning result tests, observation and response questionnaires. The validity of teaching materials by experts obtained an average score of 3.5 with very good category (valid). Legibility test results are very good, student responses in very good category, and observation of teacher and student activity in active category. The effectiveness of teaching material is high category in small group test and limited field-testing in XI IPA 3 and modium category in XI IPA 4. It shows the teaching material based on Advanced Organizer with SETS vision on colloid material for high school students has valid, practical and effectively used in the learning process. Keywords: teaching materials, Advanced Organizer, SETS, colloid material